Auditory and vestibular efferents - Ryugo, David K. (Springer handbook of auditory research,, 2011)
The biology of auditory and vestibular efferent systems encompasses a wide range of issues where exploration requires knowledge of basic anatomy, electrophysiology, and pharmacology of the inner ear.  These topics lead into discussions of development and evolution of efferent systems.  The functional significance of these systems is highlighted by an overview of central efferent anatomy, neuronal responses, and plasticity following efferent activation. Contents: • Introduction David K. Ryugo • Anatomy of Olivocochlear Neurons M. Christian Brown • Physiology of the Medial and Lateral Olivocochlear Systems John J. Guinan Jr. • Pharmacology and Neurochemistry of Olivocochlear Efferents William F. Sewell • Cholinergic Inhibition of Hair Cells Eleonora Katz, Ana Belén Elgoyhen, and Paul Albert Fuchs • The Efferent Vestibular System Joseph C. Holt, Anna Lysakowski, and Jay M. Goldberg • Development of the Inner Ear Efferent System Dwayne Simmons, Jeremy Duncan, Dominique Crapon de Caprona, and Bernd Fritzsch • Evolution of the Octavolateral Efferent System Christine Köppl • Central Descending Auditory Pathways Brett R. Schofield • Central Effects of Efferent Activation Donald Robertson and Wilhelmina H.A.M. Mulders • Corticofugal Modulation and Beyond for Auditory Signal Processing and Plasticity Nobuo Suga, Weiqing Ji, Xiaofeng Ma, Jie Tang, Zhongju Xiao, and Jun Yan About the Editors: David K. Ryugo is Professor (retired and part time) in the Departments of Otolaryngology-Head and Neck Surgery and Neuroscience at the Johns Hopkins University School of Medicine, and Curran Foundation Professor of Neuroscience at the Garvan Institute of Medical Research. Richard R. Fay is Director, Parmly Sensory Sciences Institute and Interdisciplinary Neuroscience Minor and Professor of Psychology at Loyola University of Chicago.Arthur N. Popper is Professor in the Department of Biology and Co-director of the Center for Comparative and Evolutionary Biology of Hearing at the University of Maryland, College Park. About the series: The Springer Handbook of Auditory Research presents a series of synthetic reviews of fundamental topics dealing with auditory systems. Each volume is independent and authoritative; taken as a set, this series is the definitive resource in the field. Overview -- Olivocochlear Efferents: Structure of the medial and lateral olivocochlear systems -- Olivocochlear Efferents: Physiology of the medial and lateral olivocochlear systems -- Olivocochlear Efferents: Chemistry of the medial and lateral olivocochlear systems -- Cholinergic inhibition of hair cells in the inner ear -- Vestibular Efferents -- Development of efferent systems -- Exuberant efferent innervation of the auditory receptors -- Comparative studies of the efferent system -- Descending projections -- Efferent modulation of brainstem activity -- Efferent effects on the central auditory system -- Index.